A comparison of empirical and experimental O7+, O8+, and O/H values, with applications to terrestrial solar wind charge exchange - Ian C. Whittaker; Steve Sembay (Geophysical Research Letters)
Abstract Solar wind charge exchange occurs at Earth between the neutral planetary exosphere and highly charged ions of the solar wind. The main challenge in predicting the resultant photon flux in the X‐ray energy bands is due to the interaction efficiency, known as the α value. This study produces experimental α values at the Earth, for oxygen emission in the range of 0.5–0.7 keV. Thirteen years of data from the Advanced Composition Explorer are examined, comparing O7+ and O8+ abundances, as well as O/H to other solar wind parameters allowing all parameters in the αO7,8+ calculation to be estimated based on solar wind velocity. Finally, a table is produced for a range of solar wind speeds giving average O7+ and O8+ abundances, O/H, and αO7,8+ values.